"Why is this night different from all other nights?" - Snicket, Lemony (Snicket, Lemony. All the wrong questions, 2016)
Thirteen-year-old apprentice Lemony Snicket discovers that not only does his chaperone have a secret, but the whole town of Stain'd By The Sea is keeping a secret involving a train, a statue, and an evil man.